Psychosocial Health of Junior High Schoolers after A Year of Online Learning - Jumaroh Jumaroh; Eka Budiarto (Indonesian Journal of Global Health Research, 2022)
The massive use of smartphone as the main learning tool for young learners due to Covid-19 pandemic has affected various aspects, including their psychosocial health. However, this case does not gain much attention from neither the parents nor the teachers. This study aimed to investigate the psychosocial problems faced by junior high school students associated with the overuse of smartphone after having a year of online leaning due to Covid-19 pandemic. This research was a descriptive study. The respondents were 78 junior high school students studying in Pemalang who were selected by a purposive sampling technique with two inclusive criteria: they used smartphones as the main learning media; and they had done online learning for at least one year. The collected data were analysed by a frequency distribution. The results showed that 29.12% of the respondents were psychosocially unhealthy; 22.78% of them were almost psychosocially unhealthy; and 48.1% of them were psychosocially healthy. However, only 10.1% of them did not suffer any psychosocial problems. Besides, the data showed that 65.8% of the respondents were in high risk of being addicted to smartphone. It can be concluded that most of the respondents faced psychosocial problems and were in high risk of smartphone addiction. Therefore, parents, teachers, and other related parties are expected to assist students in healing and maintaining their psychosocial health.